PENGARUH APLIKASI BAKTERI ENDOFIT PENAMBAT NITROGEN DAN PUPUK NITROGEN TERHADAP SERAPAN NITROGEN SERTA PERTUMBUHAN TANAMAN TEBU - Lusi Nurhayati Tamba; Diaz Gustomo; Yulia Nuraini (Jurnal Tanah dan Sumberdaya Lahan, 2016)
Nitrogen is a macro nutrient needed to support growth and productivity of sugarcane. Nitrogen requirement for sugarcane can be met through organic, inorganic, and biological fertilizers. The objectives of this study was to analyze the effect of N fertilizer treatments with the use of nitrogen-fixing endophytic bacteria Gluconacetobacter diazotrophicus on levels of nutrient nitrogen and the growth of sugarcane. Treatments tested in this study were P0 = control (no added fertilizer and bacteria), P1 = (800 kg N ha-1 + 5 mL bacteria inoculation), P2 = (600 kg N ha-1 + 5 bacteria inoculation), P3 = (400 kg N ha-1 + 5 mL bacteria inoculation), dan P4 = (200 kg N ha-1 + 5 mL bacteria inoculation). The results showed that treatment of N fertilizer doses did not significantly different for populations of endophytic bacteria Gluconacetobacter diazotrophicus and the vegetative growth of sugarcane. Doses of N fertilizer treatment with utilization of endophytic bacteria Gluconacetobacter diazotrophicus only significantly different on N-total and N uptake of sugarcane. Treatment in P2 (600 kg N ha-1 + Gluconacetobacter diazotrophicus 5 mL) has a larger population of Gluconacetobacter diazotrophicus endophytic bacteria than other treatments, is 53.0 x 102 cfu mL-1, and has higher levels of N-total than other treatment is 0.16%. For vegetative growth of sugarcane in P1 (800 kg N ha-1 + Gluconacetobacter diazotrophicus 5 mL) had a good influence for the high, number of leaves, dry weight and N uptake of sugarcane. While the number of tillers in P4 (200 kg N ha-1 + Gluconacetobacter diazotrophicus 5 mL) has a seedling growth more than other treatments